Microscale Variability in Biomass and Photosynthetic Activity of Microphytobenthos During a Spring-Neap Tidal Cycle - Kromkamp, Jacco C.; Morris, Ed; Forster, Rodney M. (Frontiers in Marine Science, 2020)
Carbon fixation by microphytobenthic algae of intertidal flats often dominates the total primary production of turbid, temperate estuaries. Whilst remote sensing can accurately measure the spatial distribution of photosynthetic biofilms at the mesoscale (1-300 m), variability at smaller scales requires in-situ investigation. Here, changes in biomass and photosynthetic activity of microphytobenthos (MPB) at the micro-scale (<1 m) were investigated. Biomass of MPB was estimated from repeated high resolution spectral measurements carried out at intervals along a short transect. Whilst the mean concentration of MPB remained constant over time, considerable variability in the spatial and temporal dimensions was measured. The biofilm grew and diminished along the transect over time, and net growth and loss rates could be established under natural conditions. Daily vertical migration was observed for the first time in an undisturbed sediment, and was modelled as a function of solar elevation and tidal angle. Top down factors such as grazing, or physical disturbance, play an important role in the changes in biomass. Photosynthetic activity was measured with portable fluorometers: one device used an artificial light source, the other measured the effective photosystem-II quantum efficiency (ΔF/Fm’) in-situ with solar irradiance. No evidence was found for photoinhibition, with Fv/Fm values consistently high, indicating an ability of the diatom biofilm to remain productive under periods of high irradiance. The maximum rate of photosynthesis reached artificial light was rarely achieved in-situ, even with full solar exposure. There was however a very good agreement between the predicted rate at ambient irradiance, and that actually measured. Composite photosynthesis-irradiance curves over the whole experimental period were similar, and showed the same initial slopes, but the maximum rate of relative photosynthetic electron transport (rETRm) based on the in-situ measurement was lower. When total depth-averaged primary production during low tide was calculated, the differences between methods varied between 5-13%, and were smallest when surface irradiance values were higher. These results show that the protocol used to measure the photosynthetic activity of the MPB had only minor importance on the overall productivity estimate compared to accurate knowledge of photosynthetically-active biomass and irradiance.